ENGLISH LANGUAGE COMPETENCE IS AN ESSENTIAL ELEMENT OF PROFESSIONALS: A THEORETICAL STUDY ON LISTENING A RECEPTIVE SKILL (International Journal of Food and Nutritional Sciences, 2022)
Humans have a very basic need for and activity of communication. It serves as a means of communication for the dissemination of knowledge and understanding among those around us. It may be described as formal conversation when people communicate information, opinions, ideas, sentiments, and so forth. In fact, it builds the bridges that enable us to cross boundaries and cultural, racial, and political divides. The foundation of life is communication. We all need to be able to communicate our needs, wants, choices, opinions, information, emotions, and ideas. It is a manifestation of who we are and who we are in all facets of life. These days, it is one of the requirements for hiring. High levels of communication skills are required in some fields, including human resources, public relations, marketing, sales, and customer service. Technocrats and professionals alike require them in the same way. English language proficiency is a critical skill for professionals, according to the paper being presented. Understanding that language is important to learners and can be learned through exposure to the four language skills is the focus of a theoretical study on listening as a receptive skill.